Defensive participation and efficacy of the libero in volleyball - Mesquita, I.; Manso, F. D.; Palao, J. M. (Journal of Human Movement Studies, 2007)
The inclusion of the figure of the "libero" in volleyball was done to try to increase the team's defensive potential. The objective of the present study was to analyse the association between the player that intervened in defence (libero or other player), the defensive efficacy and the counter-attack performance. A total of 960 defensive actions were analysed in 33 sets of the classificatory and final phases of the World League in 2004. The variables studied were: player that intervened in defence (libero or other player); zone of defence intervention; zone where counter-attack is made; tempo of the spike; defensive efficacy; distribution efficacy; and counter-attack efficacy. The likelihood that the spikers used the second tempo in the counterattack phase was greater when the libero defended. Likewise, the likelihood of an excellent defence occurring, which allows the team all its attack options, increased when the libero executed the defence. There is no association between the player that intervened in defence (libero or other player) and zone of attack, number of blockcrs that the hitters oppose in counter-attack and counter-attack efficacy. In summary, the intervention is associated with better efficacy in defence and with quick attacks (second tempo). However, the intervention of the libero is not associated with an improvement of the counter-attack performance of its team.